Peranan Wanita Kristen Masa Kini - Yunita Sumirah (Sekolah Tinggi Theologia Nazarene Indonesia, 2016)
The changing of how to value women in many societies and community in these last recent decades, make women aware of their position in family, social context, profession or religion context. In general speaking, women’s influence and role are not only increasing in their responsibilities at home, but also outside their home in various context. In Church context, Christian women today are also more engaged and involved in church ministries. The role of women is more and more important today. It is very important that Christian women to be wiser their priority setting.